2019
DOI: 10.1016/j.jvacx.2019.100004
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness to basement membrane extract as a possible trait for tumorigenicity characterization

Abstract: Highlights Tumorigenicity assays can be time-consuming and results can be equivocal. Basement membrane extract (BME) is known to enhance tumorigenicity. The tumorigenicity of Vero (≤p258) and ARPE-19 cells were not enhanced by BME. BME enhanced the tumorigenicity of HeLa, 293, MDCK, and transformed Vero cells. BME may be a useful reagent for characterizing vaccine cell substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Studies found that laminin-111 derived peptide YIGSR increased adhesion, migration, and decreased tumor growth, metastasis (as per a study) shown in Table 2B and invasion 9,10,23,24 . YIGSR binds to receptor 32/67 kD, which is specific for tumor cells, and hence this also serves as a potential target for cancer treatment.…”
Section: Fig 4: Targeted Therapeutic Delivery In Malignancy Using Lam...mentioning
confidence: 57%
See 2 more Smart Citations
“…Studies found that laminin-111 derived peptide YIGSR increased adhesion, migration, and decreased tumor growth, metastasis (as per a study) shown in Table 2B and invasion 9,10,23,24 . YIGSR binds to receptor 32/67 kD, which is specific for tumor cells, and hence this also serves as a potential target for cancer treatment.…”
Section: Fig 4: Targeted Therapeutic Delivery In Malignancy Using Lam...mentioning
confidence: 57%
“…AG73-liposome encapsulating diagnostic ultrasound contrast gas helped in contrast imaging to detect cancer lesions 8 . YIGSR blocked experimental metastasis formation in the lungs, prevented xenograft growth and angiogenesis 9,10 . YIGSR reduced the number of blood vessels in-vivo tumor growth 2 .…”
Section: Fig 3: Development Of the Cell-specific Targeting System Lam...mentioning
confidence: 96%
See 1 more Smart Citation
“…Trypsinized cells are placed in a culture vessel with a magnetic stirrer inhibiting cell attachment to the substrate and improve cell-cell adhesion. 141,146 Alternatively, spheroids are grown in a hanging drop deposited on a microplate lid. The cells start to aggregate due to the gravity.…”
Section: Techniques For Generating 3d Cell Culturementioning
confidence: 99%
“…172,173 They often rely on artificial ECM, like Matrigel or BME-2, to promote their selforganization. 139,141 Organoids have the capacity to grow under an in vivo condition owning to their self-renewal/self-assemble capacity. When given a scaffolding extracellular environment, they form a 3D structure that presents a similar organization and functionality as an organ.…”
Section: Organoidsmentioning
confidence: 99%